The Conserved Proline18 in the Polerovirus P3a Is Important for Brassica Yellows Virus Systemic Infection - Zhang, Xiao-Yan; Zhao, Tian-Yu; Li, Yuan-Yuan; Xiang, Hai-Ying; Dong, Shu-Wei; Zhang, Zong-Ying; Wang, Ying; Li, Da-Wei; Yu, Jia-Lin; Han, Cheng-Gui (Frontiers in Microbiology, 2018)
ORF3a, a newly identified non-AUG-initiated ORF encoded by members of genera Polerovirus and Luteovirus, is required for long-distance movement in plants. However, the mechanism of action of P3a in viral systemic movement is still not clear. In this study, sequencing of a brassica yellows virus (BrYV) mutant defective in systemic infection revealed two-nucleotide variation at positions 3406 and 3467 in the genome. Subsequent nucleotide substitution analysis proved that only the nonsynonymous substitution (C→U) at position 3406, resulting in P3aP18L, abolished the systemic infection of BrYV. Preliminary investigation showed that wild type BrYV was able to load into the petiole of the agroinfiltrated Nicotiana benthamiana leaves, whereas the mutant displayed very low efficiency. Further experiments revealed that the P3a and its mutant P3aP18L localized to the Golgi apparatus and near plasmodesmata, as well as the endoplasmic reticulum. Both P3a and P3aP18L were able to self-interact in vivo, however, the mutant P3aP18L seemed to form more stable dimer than wild type. More interestingly, we confirmed firstly that the ectopic expression of P3a of other poleroviruses and luteoviruses, as well as co-infection with Pea enation mosaic virus 2 (PEMV 2), restored the ability of systemic movement of BrYV P3a defective mutant, indicating that the P3a is functionally conserved in poleroviruses and luteoviruses and is redundant when BrYV co-infects with PEMV 2. These observations provide a novel insight into the conserved function of P3a and its underlying mechanism in the systemic infection.